2021
DOI: 10.1177/00220574211039483
|View full text |Cite
|
Sign up to set email alerts
|

Factor Associated With Teacher Satisfaction and Online Teaching Effectiveness Under Adversity Situations: A Case of Vietnamese Teachers During COVID-19

Abstract: How teachers perform and react to the world-wide pandemic and how the epidemic affects an education system may also be used as new conditions to consider the way to enhance SDG4 in developing countries. Regarding that concern, this study investigated 294 teachers’ perspective on their teaching effectiveness and satisfaction during COVID-19. The findings underlined the significant roles of support from various stakeholders, school readiness toward digital transformation, and teachers’ anxiety over teacher satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…It, therefore, implies that teachers were less satisfied and less confident while teaching online. is result corroborates the position of Pham et al [66] who argued that abrupt changes in daily routine and teaching habits, and anxiety had a significant negative impact on both teacher satisfaction and online teaching effectiveness. e finding also coincides with [35], where the author claimed that teachers' levels of satisfaction dropped and that they experienced rapid mental fatigue with the online teaching process.…”
Section: Discussionsupporting
confidence: 89%
“…It, therefore, implies that teachers were less satisfied and less confident while teaching online. is result corroborates the position of Pham et al [66] who argued that abrupt changes in daily routine and teaching habits, and anxiety had a significant negative impact on both teacher satisfaction and online teaching effectiveness. e finding also coincides with [35], where the author claimed that teachers' levels of satisfaction dropped and that they experienced rapid mental fatigue with the online teaching process.…”
Section: Discussionsupporting
confidence: 89%
“…Empirical evidence from the case of Vietnamese social work educators and students (e.g. Dinh and Nguyen, 2020 ; Pham et al, 2021 ) demonstrates that restricted access to technology resources (e.g. disrupted Internet connection and low-quality sound of the lectures) has impeded effective participation in online courses during COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, personal strains on lecturers resulting from the pandemic such as health concerns, emotional care, new family and domestic responsibilities, professional and personal plans, or household organisation are rarely put in the forefront, if at all considered. Studies have shown that Vietnamese teachers are undesirably pushed to stay more resilient to unexpected transformation in daily teaching routines caused by the pandemic ( Pham and Phan, 2021 ; Pham et al, 2021 ). Indeed, despite the volume of work and additional training needed to adjust to online teaching and assessment during COVID-19, teacher remuneration paradoxically remains unchanged ( Pham, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sudden switch to the online mode posed multiple challenges to many countries worldwide (Bergdahl & Nouri, 2021;Kovacs et al, 2021;Pham et al, 2021). It required teachers to swiftly equip themselves with digital competence to cope with the new mode(s) of delivery.…”
Section: Introductionmentioning
confidence: 99%